Embryonic Cerebrospinal Fluid Increases Neurogenic Activity in the Brain Ventricular-Subventricular Zone of Adult Mice - Alonso, Maria I.; Lamus, Francisco; Carnicero, Estela; Moro, Jose A.; de la Mano, Anibal; Fernández, Jose M. F.; Desmond, Mary E.; Gato, Angel (Frontiers in Neuroanatomy, 2017)
29 Neurogenesis is a very intensive process during early embryonic brain development, 30 becoming dramatically restricted in the adult brain in terms of extension and intensity. We 31 have previously demonstrated the key role of embryonic cerebrospinal fluid in developing 32 brain neurogenic activity. We also showed that cultured adult brain neural stem cells remain 33 competent when responding to the neurogenic influence of embryonic cerebrospinal fluid. 34 However, adult cerebrospinal fluid loses its neurogenic inductive properties. Here, by means 35 of an organotypic culture of adult mouse brain sections, we show that local administration of 36 embryonic cerebrospinal fluid in the subventricular zone niche is able to trigger a neurogenic 37 program in neural stem cells. This leads to a significant increase in the number of non- 38 differentiated neural stem cells, and also in the number of new neurons which show normal 39 migration, differentiation and maturation. These new data reveal that Embryonic 40 Cerebrospinal Fluid activates adult brain neural stem cells, supporting the previous idea that it 41 contains key instructive components which could be useful in adult brain neuroregenerative 42 strategies.